Computer aided ligand based screening for identification of promising molecules against enzymes involved in peptidoglycan biosynthetic pathway from Acinetobacter baumannii. (October 2020) - Amera, Gizachew Muluneh; Khan, Rameez Jabeer; Pathak, Amita; Jha, Rajat Kumar; Muthukumaran, Jayaraman; Singh, Amit Kumar
Abstract: A. baumannii has been considered as Priority-I as suggested by the World Health Organization (WHO) and the most critical pathogenic microorganism for causing nosocomial infection in imunno-compromised hospital-acquired patients due to multi-drug resistance (MDR). In the current study, we utilized "Computer-aided ligand-based virtual screening approach" for identification of promising molecules against Mur family proteins based on the known inhibitor (Naphthyl Tetronic Acids ((5 Z )-3-(4-chlorophenyl)-4-hydroxy-5-(1-naphthylmethylene) furan-2(5 H )-one)) of MurB from E. coli . The in-house library was prepared using a similarity search of a known inhibitor (Drug Bank ID: DB07296) against several relevant chemical databases. The molecules obtained from virtual screening of Naphthyl Tetronic Acids in-house library were successively subjected to physicochemical and ADMET screening. After this, the molecules which passed all the filters, subsequently subjected into interaction analysis with the drug target proteins (MurB, MurD, MurE and MurG) of A. baumanni and the results explained that four molecules were promising (CHEMBL468144, DB07296, Enamine_T5956969 and 54723243) for further molecular dynamics simulations. The free and ligand bounded proteins that undergone MD simulation are listed as follows: MurB, MurB-CHEMBL468144, MurB-DB07296, MurE, MurE-54723243, MurE-DB07296, MurD, MurD-Enamine_T5956969, MurD-DB07296, MurG, MurG-CHEMBL468144, and MurG-DB07296. Based on global and essential dynamics analysis, the stability order of molecules towards MurB (CHEMBL468144 > DB07296); MurD (Enamine_T5956969 > DB07296); MurE (54723243 > DB07296) and MurG (CHEMBL468144 > DB07296) indicates that the newly identified molecules are more promising one in comparison with the existing inhibitor. Based on all the docking and MD simulation results, the stability order of the free and ligand bounded protein are as follows; MurB and MurB-ligand complexes > MurD and MurD-ligand complexes > MurG and MurG-ligand complexes > MurE and MurE-ligand complexes. Finally, the selected compounds would be recommended for further experimental investigations and used as promising inhibitors of the infection caused by A. baumannii . Graphical abstract: Image 1 Highlights: A.baumannii has been considered as Priority-I as suggested by the WHO. In-house library was prepared using a similarity search of a known inhibitor. Computer-aided ligand-based virtual screening approach was performed. Identification of promising molecules against Mur family proteins.